Development of pulmonary tuberculosis in the patient with systemic sarcoidosis and brain involvement - E. V. Korzh; N. A. Podchos; S. A. Iskevich; O. E. Perederiy (Туберкулез и болезни лёгких)
The article presents a clinical case of pulmonary tuberculosis with destruction and bacterial excretion in the patient with systemic sarcoidosis and cerebral lesions. Tuberculosis was characterized by the inﬁltrate and cavity in S1+2 of the left lung, tuberculous mycobacteria were detected by microscopy, GeneXpertMBT/Rif, and culture. Systemic sarcoidosis with brain involvement was diagnosed based on intrathoracic lymphadenopathy in 2015, development of dissemination in the lungs and neurological symptoms by 2018, deterioration of changes by 2019, rapid partial resolution of foci in the lungs, and moderate regression of neurological disorders during the treatment with prednisolone. A full course of anti-tuberculosis chemotherapy (316 doses) resulted in persistent sputum conversion, resolution of the inﬁltrate and cavity healing. Prednisolone was administered simultaneously for 318 days with increased doses (45-35 mg) for the ﬁrst 2 months, then titrated down to 15 mg and remained so until the end of the treatment with gradual reduction and discontinuation. Changes in the lungs and improvement of clinical and radiological manifestations of neurosarcoidosis were documented.